Study of Antimicrobial Potency of Synthesized Cellulose-Based Nanocomposite Films Incorporating Bi-Fe-Sn Trimetallic Microcrystalline Using Terminalia arjuna Leaf Extract for Packaging and Medicinal Applications - Amara Dar; Rabia Rehman; Nimrah Jamil; Ghufrana Samin; Muhammad Muzammil Jahangir; Zahrah T. Al-thagafi; Reem I. Alsantali; Maha E. Al-Hazemi; Liviu Mitu (Journal of Chemistry, 2023)
In this work, cellulose-based nanocomposite films having trimetallic (Bi, Fe, and Sn) nanoparticles were prepared by green adaptive methodology using Terminalia arjuna leaf extract as a reducing and stabilizing agent. Then, they were characterized by FTIR and SEM. The color change of microcrystalline cellulose films revealed the formation of the trimetallic (Bi, Fe, Sn) nanoparticles. Characteristics absorption peaks for reducing functional groups indicated the presence and role of the plant material used; moreover, the presence of various bands in FTIR spectra below 1000 cm−1 was indicative of the formation of (Bi, Fe, and Sn) nanocomposites. These synthesized nanomaterials were also tested for their antimicrobial potency against Escherichia coli and Pseudomonas aeruginosa. Positive outcomes designated their potential to be adopted for biomedical applications and in food packaging as an alternative of synthetic plastics to control pollution.